Performance optimization and multi-objective analysis of an innovative solar-driven combined power and cooling system - Kumar Yadav V.; Sarkar J.; Ghosh P. (My University, 2025)
Solar-driven combined cooling and power systems are promising for hot climates, but lower performance is the main concern. Therefore, an improved new configuration is proposed to enhance its performance, which consists of a suitably located secondary ejector along with an internal heat exchanger and parabolic trough collector. The proposed system is analyzed with three different refrigerants from thermodynamic, economic, and environmental perspectives. System performance is optimized by employing a genetic algorithm. At the mean operating scenario, the best exergy efficiency and performance index are 6.92 % and 0.149, respectively. The total cost with isobutene is the lowest, nearly 16500 $/yr. The performance is at its peak in January but lowest in April at Varanasi in India. The proposed system is also compared with the individual power and cooling as well as the analogous systems. The exergy efficiency and performance index of the studied system are approximately 18% and 9% higher than those of the individual cooling and power system and nearly 98% and 68% higher than the analogous system, respectively, with isobutane. Annual total cost is 8% lower than that of the individual system and 16% lower than that of analogous system. Hence, the proposed system shows superiority for building applications. © 2024 Elsevier B.V.